Use of calcium to optimize long-term proliferation of friable embryogenic calluses and plant regeneration in Hevea brasiliensis (Mull. Arg) - Etienne H; Carron M P; Lartaud M; Michaux-Ferriere N (Journal of Experimental Botany, 1997)
In Hevea brasiliensis (Mull. Arg), increasing the calcium content of the friable callus maintenance medium from 3 to 9 mM stimulated regeneration potential through somatic embryogenesis. This stimulation could be attributed to the homogeneous cytological structure of calluses, which were formed of undifferentiated cells capable of somatic embryogenesis in optimal culture conditions. The very marked increase in the active cell population was sufficient to cause a decrease and a stabilization of water and osmotic potentials of the calluses, whereas their water content increased. The regeneration capacity of calluses cultured on a medium with additional CaCl2 was greater in terms of both quantity (number of somatic embryos produced was increased 2-fold) and quality (germination efficiency trebled). High CaCl2 concentrations (9 mM CaCl2) in the embryogenesis induction medium favoured somatic embryo development when calluses were maintained 2 months on the same medium. In this case, addition of benzylaminopurrine (BAP) and 3,4-dichlorophenoxyacetic acid (3,4-D) increased the number of embryos produced (243 embryos g -1 FW callus) and their germination capacity (27;). These culture conditions were used to determine the optimum embryogenesis induction period. The length of the period affected both the intensity of embryogenesis (maximum 56-77 d) and somatic embryo quality (maximum 49-70 d). The best results are obtained with a 70 d embryogenesis induction period, within which 355 embryos g -1 FW callus were obtained, with 35;germination.
Keywords: Calcium; Hevea brasiliensis; Histology; Long-term culture; Somatic embryogenesis; Water status